Revisiting the conflict–performance relationship in international joint ventures: the moderating role of conflict resolution strategies - Ali, Tahir; Shahzad, Khuram; Ojala, Arto (Emerald, 2026)
Purpose This research aims to explore the moderating effects of three conflict resolution strategies (CRSs), such as problem-solving, compromising and enforcing on the conflict–performance relation in international joint ventures (IJVs). The authors draw from social exchange and transaction cost theories to reconcile the contradictory empirical findings and explore the relationships among conflict, IJV performance and CRSs. Design/methodology/approach This study uses Web-based survey and collects data from 89 IJVs of Nordic firms operating across Europe, Asia and America. The collected empirical data is analyzed using multiple regression analysis to test the proposed model. Findings The key argument is that the impact of conflict on the performance of IJVs depends on how IJV partners resolve their conflicts. The authors find that conflict enhances IJV performance while using a problem-solving strategy, neither enhances nor reduces IJV performance while using a compromising strategy and reduces IJV performance while using a forcing strategy. Practical implications The authors offer several important practical insights in this research; for instance, it is insufficient to consider the extent of conflicts in isolation when examining how these conflicts impact the IJV performance. Furthermore, IJV partners should not unilaterally impose their solutions on the other partner if they want IJV to benefit from the conflicts. Originality/value This study contributes to the stream of literature dealing with issues such as conflicts and the dark side of inter-partner relationships in IJVs. The authors reconcile the contradictory empirical findings about the conflict–performance relationship resided in prior research.
Keywords: Conflict; Conflict resolution; International joint venture; International joint venture performance; Transaction cost theory; Social exchange theory; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Tuotantotalous kaupp|en=Industrial Management econ|